Ponudba gozdnih zemljišč med letoma 2003 in 2007 na območju upravnih enot: Ptuj, Slovenska Bistrica, Ruše in Radlje ob Dravi - Kopše, Igor (Gozdarski vestnik, 2008)
With the assistance of the web archive of public announcements of forest land offers on the e-government web site, 1.241 offers were analyzed on the area offour governmental units. These units represent about 8% of entire Slovenian state area. The analyzed offers refer to the time span between April 2003 and November 2007. We have ascertained that the forest land offer is the largest for the small scale surfaces up to 1 hectare. The offered prices correlate with the surface in such a way that the price expressed in /m2 is falling with the increasing offered forest land surface. The prices are higher when forest land is offered as a part of an entire farm.
Keywords: gozdovi; zemljišča; cene; vrednotenje; trgovanje; gozdarska politika